Effect of the addition of different sources of fatty acids in the pig diet on the transcriptomic profile of different tissues - Fanalli, Simara Larissa (2022)
The Sus Scrofa species is one of the most important for the production of meat and other animal products worldwide and is an animal model for metabolic diseases in humans. Furthermore, pork is one of the main sources of fatty acids (FA) in the human diet. The FA consumption is associated with fat deposition and increased occurrence of metabolic diseases. On the other hand, some studies diverge on the role of FAs involved in cellular inflammatory responses in metabolic diseases. The aim of this study was to identify differentially expressed genes (GDE) and transcription factors from muscle and liver samples from immunocastrated male pigs fed a diet added from different sources and levels of FA. Dietary treatments consisted of corn-soybean meal growing-finishing diets supplemented with 1.5% soybean oil (SOY1.5, common level used in commercial pig production) or 3% soybean oil (SOY3.0) or 3% canola oil (CO) or 3% fish oil (FO) for an experimental period of 98 days during the growing and finishing phases (18 pigs/treatment). The analysis of the parameters of the blood was performed, as well as the profile of AG deposited in the tissues. The DEG (FDR 10%) was identified in 72 samples of skeletal muscle and liver using the DESeq2 R., followed by data quality analysis. From the transcriptome analysis of skeletal muscle and liver samples, the functional enrichment analysis (FDR <0.10) by MetaCore revealed maps of signaling pathways associated with metabolic processes, oxidative stress, metabolic and neurodegenerative diseases, as well as gene networks related to immune response and biological processes. The enrichment of the basal diet with oil sources containing different FA profiles influenced the composition of the deposited profile, the blood parameters, and the gene expression in metabolic pathways and network processes in the skeletal muscle tissue and liver of animals during the growth and termination. When the comparison was related to the addition of soybean oil and fish oil, the highest amount of total DEG was identified. In addition, transcription factors related to lipid metabolism and immune response were identified when using 1.5% or 3% soybean oil. It could contribute to the nutrigenomics research field that aims to elucidate dietary interventions in animal and human health, as well as to drive food technology and Science.